Sosialisasi Peraturan Pemerintah tentang Perlindungan Tumbuhan Dan Satwa Liar untuk Mendukung Pengelolaan Hutan Desa Tuwung - Fatiqin, Awalul; Kadafi, Ahmad Muammar; Febrianto, Yahya; Kamison (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2024)
Background: The highly biodiverse Tuwung Village Forest has been the site of a productive collaboration between the village community and the government in an effort to manage a sustainable environment. The unique and rare flora and fauna in this forest have benefited significantly from this collaboration. Populations of rare species have increased, and disturbed ecosystems have also experienced significant recovery. The main objective of this collaboration is to maintain the sustainability of the environment and natural resources in Tuwung Village in line with applicable regulations, especially the Minister of Environment and Forestry Regulation No. 106. Method: Assistance using the Asset Based Community Development (ABCD) method has been adopted in the implementation of PLHD management socialization in Tuwung Village. Result: The results of the analysis show that the participants, namely the managers of KPHD Tuwung, have achieved a very good level of understanding regarding various key aspects, such as the role and function of the area protection and security section (95%), area patrol scheme (98%), animal protection status (100%), data collection and reporting (90%), and animal release (100%). Conclusion: The high level of enthusiasm from the participants reflects their commitment to implementing PLHD management concepts, which are expected to contribute significantly to sustainable environmental conservation in Tuwung Village.